Penerapan Kode Etik Jurnalistik Pada Pemberitaan Kasus Pelecehan Seksual Di Tribun Sumsel Edisi Juli-September 2022 - Suci Novita Sari; Amin Sihabuddin; Jufrizal (Jurnal Ilmu Komunikasi Dan Sosial Politik, 2023)
This research is entitled "Application of the Journalistic Code of Ethics in the Reporting of Sexual Harassment Cases in the South Sumatra Tribune, July-September 2022 Edition." in terms of language, therefore the aim of this research is to find out how the Journalistic Code of Ethics is implemented in the South Sumatra Tribune regarding sexual harassment news published from July to September 2022 on the Tribunsumsel.Com website. This research uses a qualitative approach. The theory in this research uses theoretical framework of the Journalistic Code of Ethics from PWI using 2 articles of the journalistic code of ethics including article 4 and article 5 of the journalistic code of ethics. sexual, but Article 4 of the journalistic code of ethics has not been implemented properly. The conclusion is that South Sumatra Tribune as an online media only prioritizes news speed rather than news quality, seen from some news that is written with obscene, sadistic elements, and so on.